Training Recommendation using Simple Addictive Weighting in Agriculture Product Trading Company - Oetama, Raymond; Andila, Mayang (International Journal of Science, Technology & Management, 2023)
The use of System Application and Processing (SAP) software is becoming increasingly popular among businesses, and ensuring employees receive adequate training is essential for effective use. However, there are common problems associated with SAP training, such as the lack of adequate training materials, training module quality, insufficient training facilities, and inadequate coach quality. These problems can result in employees not receiving the training they need to operate the software effectively, leading to a lack of productivity and efficiency in the workplace. To address these issues, the development of a training recommendation application using XAMPP, HTML, PHP, and CSS has been successful. The application offers an integrated, secure, and accurate solution to select the most appropriate SAP Training Module for each employee based on their performance across different attributes. The User Acceptance Testing (UAT) carried out with the Human Resource staff showed that the application built using the Simple Additive Weighting (SAW) method was 100% effective in selecting the best module for each employee. The SAW method considers the weighted sum of performance rankings for each module, providing a reliable and accurate recommendation for the most suitable module for each employee.